Acute lymphoblastic leukemia in a 2-year-old girl whose mother was previously diagnosed with antiphospholipid syndrome: a case report (2015)
Background The role of maternal exposures and conditions in the origin of childhood cancer has been a subject of growing interest, but current evidence is inconclusive. Case presentation We present a case detected in a multicenter case–control study evaluating the association between parental risk factors and childhood acute lymphoblastic leukemia (ALL). The patient is a Colombian girl who was diagnosed with ALL-L1 when she was 2 years old. Her mother had been diagnosed with antiphospholipid syndrome before pregnancy and had also been treated with subcutaneous injections of heparin. Other potentially relevant maternal and patient exposures are also reported in this paper. Conclusion We hypothesize that the maternal autoimmune disease could be a contributor in the causality network of the daughter’s leukemia. However, the role of other exposures cannot be excluded.